Case report of a fulminant non-aneurysmal convexity subarachnoid hemorrhage after COVID-19 - Maximilian Scheer (Elsevier, 2022)
We report on a case of a fulminant non-aneurysmal subarachnoid hemorrhage after COVID-19 in a patient without previous medical history or known previous illness despite a COVID-19 infection one month prior. We saw rarefied vessels in the area of the left middle cerebral artery besides a massive left frontal hemorrhage on cranial imaging. We concluded that these rarefied vessels are the expression of an RCVS, which fits the history of progressive headaches for one month. The RCVS might be caused by the COVID-19 infection and is related to the hemorrhage. Unfortunately, due to preoperative entrapment, brain death occurred a few days later.